The Implementation of The Income Tax Concept in Indonesia: The perspective of Islamic Sharia - Memed Sueb (Universitas Padjadjaran, 2021)
Tax revenue is Indonesia's primary source of income. Whereas, in Islamic law, it is allowed under compulsive conditions due to state finances deficit. The research method used is juridical normative, and literature's study data collection techniques. Research's results state the difference between tax and zakat regarding the legal basis. Income taxation in Indonesia is based on the constitution in the year 1945. It was formulated through an agreement between the executive and the legislature and manifested in a constitution. Meanwhile, the legal basis for zakat is Allah's word and manifested in the form of the Koran; Sunnah; and Ijma. Another difference is that the tax rate can change according to government policy, while the zakat rate is fixed. Additionally, the subject, object and basis of tax imposition are following Islamic Sharia